2012
DOI: 10.1007/s11882-012-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dietary Long-Chain Polyunsaturated Fatty Acids on Respiratory Illness in Infants and Children

Abstract: Increasing evidence suggests that intake of long-chain polyunsaturated fatty acids (LCPUFA), especially omega-3 LCPUFA, improves respiratory health early in life. This review summarizes publications from 2009 through July 2012 that evaluated effects of fish, fish oil or LCPUFA intake during pregnancy, lactation, and early postnatal years on allergic and infectious respiratory illnesses. Studies during pregnancy found inconsistent effects in offspring: two showed no effects and three showed protective effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
1
19
0
2
Order By: Relevance
“…A few RCTs have investigated the effect of LCPUFAsupplemented formulas on the development of allergy, with positive effects in some, but not all studies (54). It is, however, unlikely that these effects are explained by the addition of AA as other studies seem to indicate such effects in RCTs with maternal n-3 LCPUFA-supplementation, in agreement with the previously mentioned meta-analysis of all RCT of n-3 LCPUFA-supplemented lactating mothers (43) and other systematic reviews of the effect of perinatal n-3 LCPUFAsupplementation of mothers (45,46).…”
Section: Commentary Lauritzen Et Almentioning
confidence: 99%
“…A few RCTs have investigated the effect of LCPUFAsupplemented formulas on the development of allergy, with positive effects in some, but not all studies (54). It is, however, unlikely that these effects are explained by the addition of AA as other studies seem to indicate such effects in RCTs with maternal n-3 LCPUFA-supplementation, in agreement with the previously mentioned meta-analysis of all RCT of n-3 LCPUFA-supplemented lactating mothers (43) and other systematic reviews of the effect of perinatal n-3 LCPUFAsupplementation of mothers (45,46).…”
Section: Commentary Lauritzen Et Almentioning
confidence: 99%
“…In particular, the n-6 polyunsaturated fatty acid (PUFA) linoleic acid, n-3 PUFA a-linoleic acid and their long chain derivatives arachidonic acid (AA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) seem to be associated with allergic diseases. N-3 PUFAs appear to have a protective effect, while a high intake of n-6 PUFAs seemed to increase the risk of allergic diseases (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…5 Docosahexaenoic acid (DHA) has been associated with improved immune outcomes and fewer respiratory infections in infants and children. [6][7][8][9] Previous studies of children ,6 years of age in the United States have reported inadequate intake of DHA and corresponding low DHA status. 7,10 In one study, children who consumed a cow' s milk-based formula supplemented with DHA had improved DHA status and fewer respiratory illnesses, compared with children consuming unsupplemented formula.…”
mentioning
confidence: 99%